Mathematics Teachers' Responses and Perceptions in Paper Folding Activities in Teaching Mathematics - M. Atnafu (University of Sofia, 2018)
The purpose of this study was to examine Addis Ababa city schools mathematics teachers responses on the paper folding activities and perception on implementing paper folding in teaching mathematics. Exploratory survey design and quantitative and qualitative research methods were used. 75 mathematics teachers were selected by cluster and simple random sampling. Training manual activities and questionnaire were used for data collection, and analysed using mean, standard deviation, independent samples t-test and qualitative analysis. Some of the findings were the primary school teachers have better perceptions than the secondary school teachers and male teachers have better perceptions than female teachers in the importance of applying paper folding in teaching mathematics than female teachers. The primary and secondary school teachers and male and female teachers have almost similar challenges in implementing paper folding in teaching mathematics. In addition, some of the teachers challenged in drawing of perfect figures, cutting or folding the papers to get the properties of mathematical expressions. Therefore, some of the recommendations were training on paper folding should be given at the beginning of the year for mathematics teachers; paper folding is included in the design of the curriculum; and necessary materials should be provided.